Trade and growth in the relation between China and Selected African countries - Ismail, Gehad Moawad (AUC Knowledge Fountain, 2015)
China’s economic engagement with African countries has been substantially increasing, since 2001. The trade has accelerated as never before, African countries’ exports to China increased dramatically from US$ 3.1 billion in 2001 to US $31.2 billion in 2007. The growth of China – African relations has increased interest in trade, because it involves crucial issues for the development of African. Consequently, this thesis is trying to assess to what extent does Chinese state- led drive for resources in Africa, especially Sub- Saharan countries affect the economic growth of these countries. The answer to this question is quantitatively assessed, showing that those countries which are highly involved in trade with China exhibit higher growth than those which are not involved, through using t-test and regression analysis. The t-test assesses whether the means of two groups are statistically different from each other or not and the regression analysis is used to show the relation between the trade and the economic growth. The results of the thesis imply that China has opened up new economic, political, diplomatic and strategic avenues for African states, yet it isn’t limited to the African leaders but it also down to Africans, both people in power and the man on the street to negotiate on their terms, identify priorities and leverage opportunities to further their own interests.